Respuesta :
m= 1 and n = 2
( m+ n = 1 +2 = 3)
rate = K [A] [B]^2
0.2 = K * 3 * 3 ^2
0.2 = K * 3 * 9
K = 0.2 / 27
K = 7.408 * 10 ^ -3 m^-2 s^-1
( m+ n = 1 +2 = 3)
rate = K [A] [B]^2
0.2 = K * 3 * 3 ^2
0.2 = K * 3 * 9
K = 0.2 / 27
K = 7.408 * 10 ^ -3 m^-2 s^-1
Answer : The rate constant of a reaction is, [tex]7.407\times 10^{-3}M^{-2}s^{-1}[/tex]
Solution :
The general rate law expression is,
[tex]rate=k[A]^m[B]^n[/tex]
where,
k = rate constant
[A] and [B] are the concentrations
m is the order of reactant A and n is the order of reactant B
Now put all the given values in the above rate law expression, we get the value for rate constant.
[tex]0.2Ms^{-1}=k\times (3M)^1\times (3M)^2[/tex]
[tex]k=7.407\times 10^{-3}M^{-2}s^{-1}[/tex]
Therefore, the rate constant of a reaction is, [tex]7.407\times 10^{-3}M^{-2}s^{-1}[/tex]